A propensity sore‐matched study: Applying a modified chest tube drainage strategy in rapid rehabilitation following uni‐portal thoracoscopic pulmonary wedge resection. Issue 11 (28th April 2022) - Xu, Guobing; Du, Jianting; Zhang, Jiarong; Chen, Hao; Zheng, Bin; Yang, Zhang; Chen, Chun
Abstract: Purpose: This study aimed to compare the value of a modified chest tube drainage strategy to a traditional drainage strategy in single‐port thoracoscopic pulmonary wedge resection. Methods: From January 2019 to July 2021, we collected clinical data on 405 patients who underwent single‐port thoracoscopic pulmonary wedge resection in the No.1 Department of Thoracic Surgery at Fujian Medical University Union Hospital, with 121 (29.9%) cases in the modified drainage strategy group and 284 (70.1%) cases in the traditional drainage strategy group. The propensity score matching method (Match Ratio = 1:1) was used to reduce differences in clinical characteristics between the two groups. Results: Following 1:1 propensity score matching, 120 matched pairs (240 patients) were included in the study. There was no significant difference in general clinical characteristics between the two groups. There was no statistical difference in intraoperative factors except for operative times (71.42 ± 22.98 min vs. 86.80 ± 36.75 min, p  < 0.001). In terms of postoperative factors, there were significant differences in postoperative chest tube duration (0.00 ± 0.00 h vs. 32.68 ± 18.51 h, p  < 0.001), total drainage volume (143.03 ± 118.33 ml vs. 187.73 ± 140.82 ml, p  = 0.008), postoperative hospital stay (2.61 ± 0.70 days vs. 3.27 ± 1.88 days, p  < 0.001), number of additional pain relief (0.14 ± 0.40 vs. 0.42 ± 0.74, p  < 0.001), facial pain score (2.7 ± 1.8 vs. 3.6 ± 2.7, p  = 0.005) and adverse events ( p  = 0.046). Furthermore, there was a statistical difference between the two groups regarding CTCAE grade‐1 complication, but no statistical difference in CTCAE grade‐2 complication. Conclusions: A modified drainage strategy in single‐port thoracoscopic pulmonary wedge resection is safe and feasible, allowing for less postoperative rehabilitation time, pain relief, reduced postoperative pleural effusion, and reduced clinical workload. Abstract : A modified chest drainage strategy is shown. In this study, we evaluated the effect of a modified drainage strategy (MDS) in patients with single‐port thoracoscopic pulmonary wedge resection via propensity sore‐matched analysis. The results demonstrate that the application of MDS is safe and feasible, allowing for less postoperative rehabilitation time and pain relief, reduced postoperative pleural effusion, and reduced clinical workload. In addition, MDS has the potential to reduce patients' medical burden.